Etiqueta y protocolo de las secretarias y su incidencia en la atención al cliente en el Gobierno Autónomo Descentralizado Municipal San Jacinto de Buena Fe, provincia de Los Ríos, año 2015 - Enderica Orozco, Maricela Ricardina (2015)
In the competitive world tag and Protocol are the fundamental tools of every institution, the same that give them the opportunity to accept new responsibilities and challenges to different professionals, enabling them to carry out their functions efficiently and effectively, demonstrating the professionalism which is characteristic in them. The objective of this work is oriented to the secretariats, administrative officers and other authorities of the autonomous Government decentralized Municipal San Jacinto de Buena Fe, by means of a guide on the rules to be used in the personal, social and professional, how to express themselves correctly, how to appropriate dress, manners, the correct treatment to be given to the different authorities in the solemn events presentations, forms of behaviour, and treatments. Methods and techniques of research helped conclude this project, which led to make the conclusions and thus give recommendations due to be implemented by administrative staff and improve the institutional image. Key words: etiquette and protocol, secretaries, customer care.